A sequence downstream of AAUAAA is required for rabbit beta-globin mRNA 3'-end formation. - Gil, A; Proudfoot, N (1984)
The sequence AAUAAA, found 11-30 base pairs (bp) upstream of the poly(A) site of most non-histone eukaryotic messenger RNAs (mRNAs) forms an essential part of the recognition site for 3'-end processing of the primary transcript. However, the sequence AATAAA is found in transcribed regions of genes and is differentially utilized in genes containing multiple copies of the sequence within the 3'-noncoding region, suggesting that the hexanucleotide alone does not comprise a complete recognition site. Therefore, it seems likely that additional sequences are required to form a complete recognition site for 3'-end formation. We have investigated the sequence requirements for mRNA 3'-end formation using the rabbit beta-globin gene as a model system. Here we demonstrate that an additional sequence 3' to AAUAAA is required for the correct 3'-end formation of rabbit beta-globin mRNA.